Technological Specialisation of Production and Export in Europe - Dan Olteanu (Romanian Academy, National Institute for Economic Research, 2009)
Continuous specialisation of a nation, conducted by the dynamic comparative advantage, is not only the effect of free market forces accompanied by commercial openness, as it depends on many other factors, among which technological progress is essential. In this study, we try to analyse the differences in the structure and relative specialisation level of production and export, as well as the evolution of territorial concentration of production by various groups of economic activities and products. We use a sample consisting of the main European countries, the USA, Japan and China. * Study within the CEEX Programme Project No. 220/2006 Economic Convergence and Role of Knowledge in Relation to the EU Integration .
Keywords: F14; O33; O47; 330; RD&I; technological specialization; geographical concentration